Return of the spider [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2025)
Return of the Spider is the prequel to Along Came a Spider. Alex Cross uncovers a murder journal by Gary Soneji, plunging into a deadly past that was designed to trap him all along.